Instructed fear learning, extinction, and recall: additive effects of cognitive information on emotional learning of fear. Issue 5 (4th July 2017) - Javanbakht, Arash; Duval, Elizabeth R.; Cisneros, Maria E.; Taylor, Stephan F.; Kessler, Daniel; Liberzon, Israel
ABSTRACT: The effects of instruction on learning of fear and safety are rarely studied. We aimed to examine the effects of cognitive information and experience on fear learning. Fourty healthy participants, randomly assigned to three groups, went through fear conditioning, extinction learning, and extinction recall with two conditioned stimuli (CS+). Information was presented about the presence or absence of conditioned stimulus–unconditioned stimulus (CS–US) contingency at different stages of the experiment. Information about the CS–US contingency prior to fear conditioning enhanced fear response and reduced extinction recall. Information about the absence of CS–US contingency promoted extinction learning and recall, while omission of this information prior to recall resulted in fear renewal. These findings indicate that contingency information can facilitate fear expression during fear learning, and can facilitate extinction learning and recall. Information seems to function as an element of the larger context in which conditioning occurs.